Efektivitas Penggunaan Youtube dalam Meningkatkan Hasil Belajar Pendidikan Agama Islam Siswa Kelas V SDN 013 Bontang Selatan Tahun Pelajaran 2023/2024 - Aini, Baiti; Minarsih, Minarsih (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This research aims to analyze the effectiveness of using YouTube as a learning medium in improving Islamic Religious Education (PAI) learning outcomes for class V students at SDN 013 South Bontang in the 2023/2024 academic year. This research is motivated by the rapid development of digital technology which has changed the way teaching and learning in schools. The use of YouTube as a digital platform is expected to have a positive impact on PAI learning. The research method used is qualitative with a descriptive approach. Data was collected through observation, in-depth interviews and documentation. The subjects of this research were PAI teachers and fifth grade students at SDN 013 South Bontang. The research results show that using YouTube as a learning medium can improve student learning outcomes. Learning videos available on YouTube allow students to understand the material better through interactive visualizations and explanations. In addition, the use of YouTube also facilitates independent learning where students can access material anytime and anywhere. However, the effectiveness of using YouTube is also influenced by several factors such as the availability of internet access, the teacher's ability to select and present relevant content, and support from parents in accompanying children while studying. Thus, this research concludes that YouTube can be an effective tool in PAI learning in the digital era, as long as it is supported by adequate infrastructure and active involvement from all related parties. This research contributes to the development of learning strategies that are innovative and relevant to current technological developments.